Investigating the Effect of Watching English Movies on Students’ English Achievement - Komaria, Winda; Sunarti; Rahmawati, Yeni (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study investigated the impact of English movie subtitles on grammar acquisition among English language learners. The study, conducted using a within-subjects design, involved 28 eleventh grade students at SMA Negeri 2 Tenggarong Seberang during the 2025/2026 school year. The participants watched the same English movie twice-once with subtitles and once without subtitles-using a balanced sequence and a one week washout period to reduce carryover effects. Grammar proficiency, specifically focusing on simple present tense, simple past tense, and present continuous tense, was assessed through an expert-validated multiple-choice test administered as a pre-test and two post-tests. Data were analyzed using a paired-samples t-test. The results showed a significant improvement in students’ grammar scores after watching with subtitles was 79.00, while the mean score after watching without subtitles was 78.11. The p values for both post-tests were below 0.05 (p = 0.001), leading to the rejection of H0 and acceptance of the alternative hypothesis (Ha). These findings indicate that subtitles play an important role in improving grammar acquisition, which confirms that subtitled movies are an effective tool for improving grammar skills among EFL students.